Echocardiographic findings of large patent ductus arteriosus in the very low birthweight infant before and after treatment with indomethacin. Issue 10 (October 1979) - Halliday, H L; Hirata, T; Brady, J P
Abstract : 17 very low birthweight infants (mean birthweight 850 g) with large patent ductus arteriosus (PDA) were studied by echocardiography before and after treatment with indomethacin. Before treatment left heart dimensions were increased suggesting large left-to-right shunt. Echographic measurements of augmented left ventricular (LV) contraction could be attributed to increase in preload, and reduction in afterload in PDA. After indomethacin, in infants showing clinical response, left heart dimensions returned rapidly to normal and LV contraction became normal or reduced. Two infants had reduced LV contraction with persistent pulmonary oedema suggesting LV failure. In contrast, infants showing no clinical response to the drug also had no significant changes in echographic measurements. Right ventricular systolic time intervals (RPEP/RVET) did not alter after indomethacin treatment in either group, suggesting that the drug does not increase pulmonary vascular resistance.